61.8k views
23 votes
Solve the following using distributive property:
9(x+3)=4x-3​

2 Answers

13 votes

Answer:

x = -6

Step-by-step explanation:

distribute 9(x+3) = 9x+27

9x+27 = 4x-3 subtract -27 and -4x on each side

9x-4x = -3-27 combine like terms

5x = -30 divide by 5

x = -6

User Dirkgently
by
6.5k points
10 votes

Answer:

x = -6

Step-by-step explanation:

⇒ 9(x + 3) = 4x - 3​

apply distributive method: a(b + c) = ab + ac

⇒ 9(x) + 9(3) = 4x - 3

multiply variables

⇒ 9x + 27 = 4x - 3

collect like terms

⇒ 9x - 4x = -3 - 27

subtract like terms

⇒ 5x = -30

divide both sides by 5

⇒ x = -6

User Will WP
by
6.0k points